Chirping for Large-Scale Maritime Archaeological Survey: A Strategy Developed from a Practical Experience-Based Approach. (29th January 2014) - Grøn, Ole; Boldreel, Lars Ole
Abstract : Archaeological wrecks exposed on the sea floor are mapped using side-scan and multibeam techniques, whereas the detection of submerged archaeological sites, such as Stone Age settlements, and wrecks, partially or wholly embedded in sea-floor sediments, requires the application of high-resolution subbottom profilers. This paper presents a strategy for cost-effective, large-scale mapping of previously undetected sediment-embedded sites and wrecks based on subbottom profiling with chirp systems. The mapping strategy described includes (a) definition of line spacing depending on the target; (b) interactive surveying, for example, immediate detailed investigation of potential archaeological anomalies on detection with a denser pattern of subbottom survey lines; (c) onboard interpretation during data acquisition; (d) recognition of nongeological anomalies. Consequently, this strategy differs from those employed in several detailed studies of known wreck sites and from the way in which geologists map the sea floor and the geological column beneath it. The strategy has been developed on the basis of extensive practical experience gained during the use of an off-the-shelf 2D chirp system and, given the present state of this technology, it appears well suited to large-scale maritime archaeological mapping.